Scientific Supervision and TPACK Competence on Teachers' Ability to Design IPAS Learning - Mardiana Mardiana; Yunus, Muh.; Elpisah Elpisah; Suarlin Suarlin (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study aims to: (1) determine the effect of academic supervision on teachers’ ability to design IPAS learning at elementary schools in Mandalle District; (2) examine the effect of TPACK competence on teachers’ ability to design IPAS learning; and (3) analyze the simultaneous influence of academic supervision and TPACK competence on teachers’ ability to design IPAS learning. The research was conducted in elementary schools across Mandalle District from September to October 2025 using a quantitative approach and a causal-comparative (ex post facto) design. A total of 51 teachers were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using PLS-SEM with the SmartPLS application. The results indicate that: (1) academic supervision has a positive and significant effect on teachers’ ability to design IPAS learning (β = 0.168; T = 2.623; p = 0.009), although the effect size is categorized as small (f² = 0.071); (2) TPACK competence has a very strong and significant effect on teachers’ ability to design IPAS learning (β = 0.827; T = 14.299; p = 0.000) with a very large effect size (f² = 3.351), making it the dominant factor influencing lesson design quality; and (3) jointly, academic supervision and TPACK competence explain 85.5% of the variance in teachers’ ability to design IPAS learning, highlighting the importance of synergy between external guidance through supervision and internal teacher competence in mastering TPACK..